2014
DOI: 10.1002/nml.21099
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Compensation of Nonprofit Executive Directors: Examining the Influence of Performance and Organizational Characteristics

Abstract: In this study we aimed to provide a better understanding of executive compensation in nonprofit organizations. We examined factors including organizational size, market, subsector, organizational type, staffing level, and organizational performance as potential influences driving variation across the nonprofit sector. The models utilize data on the population of nonprofit organizations required to file Form 990 returns with the Internal Revenue Service in order to broadly examine compensation. The results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 28 publications
3
24
0
5
Order By: Relevance
“…Baber, Daniel, and Roberts () found that changes in executive compensation are positively associated with changes in the program ratio, and infer that the program ratio may be used to monitor managers’ performance, with managers rewarded for taking actions to increase reported program expenses. Grasse, Davis, and Ihrke () found that executive compensation is positively associated with the program ratio, which appears to support Baber et al’s () inference. In Madigan v. Telemarketing Associates, Inc .…”
Section: Incentives For Managing the Program Ratiomentioning
confidence: 68%
“…Baber, Daniel, and Roberts () found that changes in executive compensation are positively associated with changes in the program ratio, and infer that the program ratio may be used to monitor managers’ performance, with managers rewarded for taking actions to increase reported program expenses. Grasse, Davis, and Ihrke () found that executive compensation is positively associated with the program ratio, which appears to support Baber et al’s () inference. In Madigan v. Telemarketing Associates, Inc .…”
Section: Incentives For Managing the Program Ratiomentioning
confidence: 68%
“…Previous examinations of the relationship between relative CEO compensation and organizational performance have found mixed results (Frumkin & Keating, 2010;Grasse, Davis, & Ihrke, 2014;Carroll, Hughes, & Luksetich, 2005). We believe this may be because these studies typically use a "market worth" variable comprised of multiple inputs such as 161 organizational performance.…”
Section: Hypothesesmentioning
confidence: 93%
“…Given the varying conclusions about the pay-performance relationship, Grasse et al (2014) inferred that different types of nonprofits may be sensitive to different measures of performance. On the one hand, Baber, Daniel, and Roberts (2002) noted that, despite the fact that performance oftentimes is difficult to quantify, they found a positive correlation between program spending and managers' compensation in a sample of charitable organizations in Maryland, assuming that managers are rewarded for increases in direct program spending.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We estimated Equations (1)-(3) on our pooled time-series data using generalized least squares (GLS) random effects models with robust standard errors, thus mitigating against omitted variables bias, autocorrelation and heteroscedasticity. GLS random effects models have been used to examine CEO compensation in prior studies (Combs et al, 2010;Grasse et al, 2014). Table V presents trends relating to executive compensation in terms of mean, median, maximum and minimum summary statistics of the independent and dependent variables.…”
Section: Description Of Variables and Their Measurementsmentioning
confidence: 99%